A 9-Year Old Boy with Leukemia and Oral Manifestation: A Case Report and Review of Literature: - Gharib, Behdad; Safari, Alieh; Kompani, Farzad; Memarian, Sara; Monajemzadeh, Maryam; Khosravi, Rahman (Galen Medical Journal, 2016)
Background: Childhood leukemia is not a common disease. However, the most common malignant neoplasms in children are the leukemias, and 77% of these cases are acute lymphoblastic leukemia (ALL). Case Report: We report a case of precursor B-cell ALL, initially presented by unusual manifestations such as; teeth ache, loose teeth and gum swelling, knee pain and a normal cell blood count (CBC). It was first considered to be Histiocytosis. Several laboratory workups have been performed to rule out the immunologic, infectious and rheumatologic diseases. A bone marrow aspiration revealed the diagnosis of leukemia. However, acute myeloid leukemia is more famous for being accompanied by oral presentation; our patient was afflicted by ALL. The patient was first referred to a dentist for the oral manifestations. Conclusion: This case reminds the importance of systemic evaluation of localized signs and symptoms in children and detailed history taking, follow-ups and physical examination.[GMJ.2016;5(4):215-18]